Biceps disorder rehabilitation for the athlete: A continuum of moderate- to high load exercises - Borms, D.; Ackerman, I.; Smets, P.; Van den Berge, G.; Cools, A. M. (The American Journal of Sports Medicine, 2017)
Background: Progressive biceps loading is recommended in the nonoperative and operative rehabilitation of biceps-related disorders. Previous researchers have proposed a continuum of exercises with low to moderate biceps loads to be used in the early and intermediate phases of rehabilitation. A progression of exercises with moderate to high biceps loads to be used in the more advanced phases of rehabilitation is lacking. Purpose: To describe a progression of exercises with progressive moderate to high loads on the biceps brachii (BB) based on electromyographic (EMG) analysis. Study Design: Controlled laboratory study. Methods: The EMG activity of BB and triceps brachii; upper trapezius, middle trapezius, and lower trapezius; and serratus anterior was determined with surface electromyography in 30 asymptomatic participants during 11 exercises. Results: Of the 11 exercises, 4 (arm shake with an Xco-trainer, lateral pull-down in pronation, chest shake with an Xco-trainer, lateral pull-down in supination) showed low (<20% maximal voluntary isometric contraction [MVIC]), 5 (pull-up in pronation with Redcord, air punch, forward flexion in supination, pull-up in supination with Redcord, inclined biceps curl) showed moderate (between 20%-50% MVIC), and 2 (throwing forward flexion, reverse punch) showed high (>50% MVIC) EMG activity in the BB. These exercises were ranked with an increasing level of activity in the BB. Conclusion: The continuum of exercises with moderate to high biceps activity may be applied in the more advanced phases of treatment for biceps disorders. In addition, biceps muscle activity may be targeted by (1) sagittal plane elevation; (2) elbow flexion with supination, without upper arm support; (3) biceps contraction from an elongated position; or (4) high-velocity, explosive exercises. Clinical Relevance: These findings may assist clinicians to select appropriate exercises to be used in the more advanced phases of nonoperative or postoperative rehabilitation of overhead athletes with biceps-related injuries.